Clinical incidents involving students on placement: an analysis of incident reports to identify potential risk factors. Issue 2 (June 2015) - Gaida, J.E.; Maloney, S.; Lo, K.; Morgan, P.
Abstract: Background: Students are sometimes involved in incidents during clinical training. To the authors' knowledge, no quantitative studies of incidents specifically involving physiotherapy students on clinical placement are available in the literature. Methods: A retrospective audit (2008 to 2011) of incident reports involving physiotherapy students was conducted to identify the nature and features of incidents. The study aimed to determine if injuries to a student or patient were more or less likely when the supervisor was in close proximity, and whether students with lower academic performance in their preclinical semester were more likely to be involved in an incident. Results: There were 19 care-delivery-related and three equipment-related incidents. There were no incidents of violent, aggressive or demeaning behaviour towards students. The incident rate was 9.0/100, 000 student-hours for third-year students and 6.8/100, 000 student-hours for fourth-year students. The majority of incidents (55%) occurred from 11 am to 12-noon and from 3 pm to 3.30 pm. Incidents more often resulted in patient or student injury when the supervisor was not in close proximity (approximately 50% vs approximately 20%), although the difference was not significant ( P = 0.336). The academic results of students involved in incidents were equivalent to the whole cohort in their preclinical semester mean 75 [standard deviation (SD) 6] vs 76 (SD 7); P = 0.488. Conclusions: The unexpected temporal clustering of incidents warrants further investigation. Student fatigue may warrant attention as a potential contributor; however, contextual factors, such as staff workload, along with organisational systems, structures and procedures may be more relevant. The potential relationship between supervisor proximity and injury also warrants further exploration. The findings of the present study should be integrated into clinical education curricula and communicated to clinical educators.